Trying to Wear the White Hat: Nixon, the Media, and the Chisum -Charles Manson Imbroglio. Issue 4 (November 2015) - Soares, John
Abstract: In August 1970, President Richard Nixon blundered—and drew media fire—when he tried to score political points by contrasting John Wayne's Chisum with accused murderer Charles Manson. In this episode, both Nixon and the press acted like the complex protagonists common in Western films in the era of the New Gray West.